PENGARUH METODE SUKU KATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA PESERTA DIDIK KELAS 1 SDN 1 ASTANA - Kusila, Asih Wahyuningsihi; Prabawati Nurhabibah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this study is the low initial reading ability of students who still have difficulty in recognizing letters, syllables, and forming simple words and sentences. This study also aims to determine the effect of the syllable method on the initial reading ability of grade 1 students at SDN 1 Astana. The syllable method was chosen because it is considered more effective in helping students recognize word structures gradually and systematically. This study uses a quantitative approach with a Nonequivalent Control Group Design. The sample consisted of two classes, namely the experimental class (30 students) who were given treatment using the syllable method, and the control class (30 students who used the regular learning method. Data collection techniques were carried out through observation and tests (pretest and posttest). The results of the study showed a significant increase in students' initial reading abilities. The average pretest score of the experimental class was 64.00, increasing to 73.07 in the posttest. Meanwhile, the control class only experienced an increase from an average pretest score of 68.60 to 67.30 in the posttest. Thus, it can be concluded that the syllable method has a positive and significant effect on improving the initial reading abilities of grade 1 students at SDN 1 Astana.